Standardized ileal amino acid digestibility of high-oleic full-fat soybean meal in broilers - Muhammad Ali; Michael Joseph; Maria Camila Alfaro-Wisaquillo; Gustavo Adolfo Quintana-Ospina; Danny Patiño; Lina-Maria Peñuela-Sierra; Thien Vu; Rouf Mian; Earl Taliercio; Ondulla Toomer; Edgar Orlando Oviedo-Rondón (Poultry Science, 2023)
ABSTRACT: High-oleic (HO) soybean may serve as a value-added feed ingredient to enrich poultry meat due to its fatty acid content. However, the amino acid (AA) nutrient digestibility of soybean meal (SBM) made from these soybeans has yet to be determined. The objective of this study was to determine apparent ileal AA digestibility (AID) and standardized ileal AA digestibility (SID) of high-oleic full-fat (HO-FF) SBM compared to normal oleic full-fat (NO-FF), normal oleic extruded expeller (NO-EE), and solvent-extracted SBM (SE-SBM) in broilers. A nitrogen-free basal diet (NFD) was fed to 1 treatment group with 10 chicks/cage to determine basal endogenous losses (BEL). Titanium dioxide was used as an inert marker. The test diets contained 57.5% of the basal NFD and 42.5% of 1 of the 4 soybean sources. A total of 272 Ross-708 male broilers were placed in 40 battery cages with 5 treatments and 8 replicates per treatment. A common starter diet was provided to all the chickens for 14 d. Experimental diets were provided as a mash for 9 d before sample collection. Chickens were euthanized with CO2 on d 23, and contents of the distal ileum were collected, frozen, and freeze-dried. The BEL were similar to the values found in the literature. At d 23, broilers fed the SE-SBM had the highest body weight gain and best FCR compared to chickens fed the HO-FF and NO-FF treatments (P < 0.001). Broilers fed the SE-SBM and NO-EE experimental diets had (P < 0.001) higher apparent ileal AA digestibility and AA SID than broilers fed the HO-FF and NO-FF treatments. In conclusion, the SID of AA from HO-FF is similar to the digestibilities of other full-fat soybeans found in the literature and is lower than that of NO-EE and SE-SBM.